Servant of earth - Hawley, Sarah (Shards of magic, 2024)
"In the underground Fae realm, only the strongest and most ruthless have power--but a young human woman forced into a life of servitude is about to change everything. Kenna Heron is best known in her village for being a little wild--some say half-feral--but she'll need every ounce of that ferocity to survive captivity in the cruel Fae court. Trapped as a servant in the faeries' underground kingdom of Mistei, Kenna must help her new mistress undertake six deadly trials, one for each branch of magic: Earth, Fire, Light, Void, Illusion, and Blood. If she succeeds, her mistress will gain immortality and become the heir to Earth House. If she doesn't, the punishment is death--or both mistress and servant. With no ally but a sentient dagger of mysterious origins, Kenna must face monsters, magic, and grueling physical tests. But worse dangers await her underground, and soon Kenna gets caught up in a secret rebellion against the inventively sadistic faerie king. When her feelings for the rebellion's leader turn passionate, Kenna must decide if she's willing to risk her life for a better world and a chance at happiness"--